ANALISIS KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA KRISTEN DALAM MENYUSUN PERENCANAAN PEMBELAJARAN DI SMPN 2 KESU’ - Devi Rungsa; Kurniaty Rara’ Lebang; Hesti Sry Putri T (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
This study aims to determine teacher competence in preparing lesson plans at SMP Negeri 2 Kesu'. This study uses a qualitative method. From this research, there were two people who were the subjects, namely the Principal of SMP Negeri 2 Kesu' and the PAK Teacher of SMP Negeri Kesu'. The background to this research is that researchers found PAK teachers who ignored their competencies, starting from not preparing lesson plans, so that the learning process was not conducive when teaching in class. From the competencies possessed by PAK teachers, it is very influential for students not only for each student but also for other people both from other teachers and also for students' parents, so that it is very important for every teacher including the teacher to understand. PAK in SMP Negeri 2 Kesu'. Based on the research results, Christian religious education teachers have been able to prepare lesson plans by paying attention to matters related to lesson planning.